2019
DOI: 10.1155/2019/7067619
|View full text |Cite
|
Sign up to set email alerts
|

Methane Alleviates Acetaminophen-Induced Liver Injury by Inhibiting Inflammation, Oxidative Stress, Endoplasmic Reticulum Stress, and Apoptosis through the Nrf2/HO-1/NQO1 Signaling Pathway

Abstract: Acetaminophen- (APAP-) induced hepatic injury is an important clinical challenge. Oxidative stress, inflammation, apoptosis, and endoplasmic reticulum stress (ERS) contribute to the pathogenesis. Methane has potential anti-inflammatory, antioxidant, and antiapoptotic properties. This project was aimed at studying the protective effects and relative mechanisms of methane in APAP-induced liver injury. In the in vivo experiment, C57BL/6 mice were treated with APAP (400 mg/kg) to induce hepatic injury followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 38 publications
2
54
0
Order By: Relevance
“…Nrf2 is a key signaling pathway that protects against inflammation by regulating the expression of antioxidant enzymes, including HO-1 and NOQ1 [ 34 ]. In particular, HO-1 exerts an anti-inflammatory effect by inhibiting NF-κB signaling via the production of carbon monoxide, a metabolite of the heme reaction [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is a key signaling pathway that protects against inflammation by regulating the expression of antioxidant enzymes, including HO-1 and NOQ1 [ 34 ]. In particular, HO-1 exerts an anti-inflammatory effect by inhibiting NF-κB signaling via the production of carbon monoxide, a metabolite of the heme reaction [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, genetically manipulating the H 2 S-producing enzymes in mammalian cells could not exclude the biological effects of endogenous H 2 S produced by sulphate-reducing bacteria in animals. In addition, CH 4 is another by-product of H 2 metabolism derived from methanogenic bacteria, and Mihaĺy Boros group found that CH 4 can also be produced by rat liver mitochondria, it has hepatic protective effects by exogenous supplement (Ghyczy et al, 2008;Ye et al, 2015;He et al, 2016;Strifler et al, 2016;Yao et al, 2017;Feng et al, 2019;Li et al, 2019a;Li et al, 2019b), however, the hepatic functions of endogenous CH 4 produced by methanogenic bacteria or by hepatocytes are not clear. As that H 2 , H 2 S, and CH 4 are endogenous gas molecules, they may exist as colonic gas mixture and transport into liver by blood circulation or free diffusion, H 2 S and CH 4 can also be produced in liver.…”
Section: Discussionmentioning
confidence: 99%
“…Dihydroethidium (DHE) staining was preformed to assess the ROS production as described in a previous study [ 27 ]. In addition, placenta tissues and HUVEC concentrations of superoxide dismutase (SOD), catalase (CAT) malondialdehyde (MDA), and glutathione (GSH) were measured using commercially available kits.…”
Section: Methodsmentioning
confidence: 99%